2019
DOI: 10.1007/s12350-017-1175-6
|View full text |Cite
|
Sign up to set email alerts
|

Compared vulnerabilities to small cardiac motions between different cameras used for myocardial perfusion imaging

Abstract: 1.8, Discovery: 0.7, DSPECT: 0). However, this vulnerability to motion was markedly (1) decreased for Conv.SPECT reconstructed without the recommended Resolution Recovery algorithm and (2) increased for DSPECT reconstructed without the recommended cardiac model. CZT-cameras and especially the DSPECT appear less vulnerable to small cardiac motions than Anger-cameras although these differences are strongly dependent on reconstruction parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To date, CZT-SPECT studies published on brain perfusion [ 18 , 20 ] or on dopamine receptors [ 32 ] are scarce and involve only very limited study populations. However, the superiority of CZT-based detectors over the NaI-scintillator systems utilized by current Anger cameras has already been clearly established, even in the clinical routine of SPECT investigations, although mostly for dedicated cardiac cameras [ 21 , 33 , 34 ]. In previous cardiac SPECT studies, dedicated cardiac CZT cameras were shown to provide significant enhancements in image quality and especially, in spatial resolution and image contrast [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, CZT-SPECT studies published on brain perfusion [ 18 , 20 ] or on dopamine receptors [ 32 ] are scarce and involve only very limited study populations. However, the superiority of CZT-based detectors over the NaI-scintillator systems utilized by current Anger cameras has already been clearly established, even in the clinical routine of SPECT investigations, although mostly for dedicated cardiac cameras [ 21 , 33 , 34 ]. In previous cardiac SPECT studies, dedicated cardiac CZT cameras were shown to provide significant enhancements in image quality and especially, in spatial resolution and image contrast [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SH is performed using 32 subsets and iterated 9 times. Inter-iteration filtering is applied by convolution with a smoothing kernel with a central value of (1 − ω ), where ω is 0.125 [ 17 , 18 ]. The only distinction between the two reconstruction protocols is the number of iterations.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Originally, all SPECT systems consisted of one or more Anger detectors that rotated about the patient, so that abrupt patient motion in the caudal direction (corresponding to the ''z'' direction in the paper by Salvadori et al 4 ) produced image data at those projections that are inconsistent with the image counts acquired at other projections. Reconstruction algorithms that are provided with data that are inconsistent from one projection to another often produce artifactual regional decreases in apparent myocardial perfusion that are misinterpreted as genuine perfusion defects.…”
mentioning
confidence: 99%
“…4 Generally speaking, among the various types of potential imaging artifacts, those due to patient motion are particularly troubling because of the wide variability of their effects on scans. Whereas center-of-rotation calibration errors and single detector camera tilt errors produce highly predictable artifactual perfusion pattern problems, 10 the effects of patient motion are highly variable, since patients can move in numerous ways that include twisting, slumping, sliding, spasming, and coughing motions at different times and at different projection angles during the course of the acquisition.…”
mentioning
confidence: 99%